Sex differences in the behavioral inhibition system and ventromedial prefrontal cortex connectivity. Issue 6 (27th October 2021) - Jung, Wi Hoon; Lee, Tae Young; Kim, Minah; Lee, Junhee; Oh, Sanghoon; Lho, Silvia Kyungjin; Moon, Sun-Young; Kwon, Jun Soo
Abstract: The reinforcement sensitivity theory proposes brain–behavioral systems that underlie individual differences in sensitivity to punishment and reward. Such trait sensitivity is assessed using the behavioral inhibition/activation system (BIS/BAS) scales. Recent studies have reported sex-linked neuroanatomical correlates of the BIS/BAS, especially in the regions belonging to the valuation and salience networks that are associated with the representation of subjective value (SV), whereas less effort has been focused on investigating the neurofunctional aspects associated with sex differences in the BIS/BAS. We tested whether functional connectivity (FC) of the regions associated with the representation of SV mediates the relationship between sex and BIS sensitivity in healthy young adults by using resting-state functional magnetic resonance imaging data and self-reported BIS/BAS measures. Compared with males, females had heightened BIS sensitivity and increased FC between the ventromedial prefrontal cortex (vmPFC) seed and posterior parietal areas; this FC mediated the impact of sex on BIS sensitivity. Given that the observed vmPFC FC maps are considered part of the default-mode network, which is involved in ruminative processes, and that the BIS is associated with rumination and negative affect, our results may have implications for psychiatric disorders such as depression and anxiety, both of which have high incidence in females.